PENGARUH WORK LIFE BALANCE TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN YANG SUDAH MENIKAH - Conchita V. latupapua; Agusthina Risambessy; Chintia Tahanora (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
This study aims to determine the effect of work life balance on organizational commitment with job satisfaction as a mediating variable for married employees at PT. Bank Maluku Malut Ambon Main Branch. The population in this study were all married employees at PT. Bank Maluku Malut Ambon Main Branch. The sample in this study were 45 employees who were married. The sampling technique used is the Purposive Sampling Technique. Methods of collecting data with a questionnaire. The questionnaire was tested for validity and reliability before collecting research data. Data was processed with SmartPLS 3.0, analyzed with Convergent Validity, Discriminant Validity, Composite Reliability, Average Variance Extracted (AVE), Path Coefficient Test, Coefficient of Determination, Hypothesis Testing using Bootstrap, and direct and indirect effect testing using Structural Equation Modeling (SEM) . The results of this study indicate that the work life balance variable has a positive and significant effect on job satisfaction. Job satisfaction variable has a positive and significant effect on organizational commitment. Work life balance has no significant effect on organizational commitment. While the variable job satisfaction is able to mediate the effect of work life balance on organizational commitment.